Geometry optimization and characterization of three-phase medium frequency transformer for 10kVA isolated DC-DC converter - Lee, Youngsil; Vakil, Gaurang; Watson, Alan James; Wheeler, Patrick (2017)
Three-phase Dual Active Bridge converter is advisable for the High-power DC-DC conversion system.